2010
DOI: 10.1007/s00253-010-2901-z
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of rhamnolipid production capacity of Pseudomonas aeruginosa PAO1 in comparison to the rhamnolipid over-producer strains DSM 7108 and DSM 2874

Abstract: A lack of understanding of the quantitative rhamnolipid production regulation in bioreactor cultivations of Pseudomonas aeruginosa and the absence of respective comparative studies are important reasons for achieving insufficient productivities for an economic production of these biosurfactants. The Pseudomonas strains DSM 7108 and DSM 2874 are described to be good rhamnolipid over-producers. The strain PAO1 on the other hand is the best analyzed type strain for genetic regulation mechanisms in the species P. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
37
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 95 publications
(40 citation statements)
references
References 38 publications
2
37
0
1
Order By: Relevance
“…Among these groups, the most common BSs that have been studied till date, are the glycolipids and the lipopeptides produced by Pseudomonas aeruginosa and Bacillus subtilis strains, respectively (Gudiña et al 2015). Glycolipids, the most popular biosurfactants, are composed of a hydrophobic moiety (long chain fatty acid) in combination with a hydrophilic moiety of carbohydrate (Muller et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Among these groups, the most common BSs that have been studied till date, are the glycolipids and the lipopeptides produced by Pseudomonas aeruginosa and Bacillus subtilis strains, respectively (Gudiña et al 2015). Glycolipids, the most popular biosurfactants, are composed of a hydrophobic moiety (long chain fatty acid) in combination with a hydrophilic moiety of carbohydrate (Muller et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…aeruginosa is one of the most popular strains employed for fermentation to produce glycolipid (Lee et al, 2008;Pornsunthorntawee et al, 2008;Huang et al, 2009;Qiang et al, 2009;Yin et al, 2009;Arutchelvi and Doble, 2010;Hazra et al, 2011;Muller et al, 2011;Saikia et al 2011). The reason might be that P. aeruginosa was easier comparatively to isolate and screen, easier to culture (results from this study showed that the growth period to reach exponential phase by batch seed culture was only about 8 to 10 h), and the higher yield of biosurfactant.…”
Section: Resultsmentioning
confidence: 86%
“…10,38,47 Despite the diversity of the reported RL structures, there are relatively few studies which both quantitatively and qualitatively analyzed RLs. 7,38,43,[47][48][49] The composition of RL mixtures produced is important, since this defines the physicochemical properties of the products, which further impacts on their potential application.…”
Section: Compositionmentioning
confidence: 99%